Characterization of delignified woods modified with ε -caprolactone - Özlüsoylu, Şeyma; Can, Ahmet; Ganguly, Sauradipta (Elsevier, 2026)
This study explores the use of deep eutectic solvents (DES) for selective lignin removal from wood, followed by in situ polymerization of ε-caprolactone (ε-CL) to enhance structural and functional properties of wood. Scots pine (Pinus sylvestris L.) and beech (Fagus orientalis) were treated with DES formulations based on choline chloride (ChCl) combined with oxalic acid (OA) or glycerol (GL) at molar ratios of 1.5:1 or 1:1, respectively. Post-treatment, ε-CL was grafted onto the delignified wood via ring-opening polymerization. Beech specimens treated with OA-based DES exhibited high mass loss and low weight percent gain (WPG: 60 %) which was different for Scots pine where lower mass loss and higher WPG (143.45 %) was observed, possibly indicating a more efficient CL grafting. The modified wood of both the species, exhibited improved water resistance and dimensional stability, with swelling values below 10 % and remarkably reduced water uptake rates. Anti-swelling efficiency exceeded 54 % in beech and 35 % in pine. FTIR confirmed successful CL grafting through ester carbonyl bands, while XRD indicated reduced crystallinity, suggesting increased amorphous character; potentially justifying the use of DES-assisted delignification and CL polymerization for functional wood modification.
Keywords: deep eutectic solvent; delignification; ε-caprolactone (ε-CL); wood modification